2021
DOI: 10.21203/rs.3.rs-1189936/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrification Potential of U.S. Industrial Boilers and Assessment of the GHG Emissions Impact

Abstract: Electrification is a key strategy for decarbonizing the industrial sector. Industrial process heating, which still relies heavily on fossil fuel combustion and accounts for the majority of sector wide GHG emissions, is a particularly attractive electrification target. Electrifying industrial boilers represents a cross-cutting opportunity for GHG emissions reductions, given their widespread use in most manufacturing industries. Yet, there are gaps in the understanding of the current population of conventional i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…At present, there are case studies missing but several companies offer electrical boilers for food manufacturing (e.g., Fulton Boiler Works, UK; LAARS Heating Systems Co., USA). In addition, a recent analysis concluded that especially the food sector has a high potential for electrification of boilers in the United States (Schoeneberger et al., 2022).…”
Section: Electrical Heatingmentioning
confidence: 99%
“…At present, there are case studies missing but several companies offer electrical boilers for food manufacturing (e.g., Fulton Boiler Works, UK; LAARS Heating Systems Co., USA). In addition, a recent analysis concluded that especially the food sector has a high potential for electrification of boilers in the United States (Schoeneberger et al., 2022).…”
Section: Electrical Heatingmentioning
confidence: 99%
“…Hence this study assumes a linear trend, as shown in Figure 11, to achieve the aforementioned targets. Schoeneberger et al (2021) estimate that the U.S. boiler population consists of approximately 38,500 units with a total cumulative capacity of 490 GW input. As per their estimates, the total industrial boiler capacity has increased by approximately 6% in recent years compared to the level in 2005 (EEA, 2005;Schoeneberger et al, 2021).…”
Section: Co 2 Emissions In Industrial Boilers and Electricity Generationmentioning
confidence: 99%
“…Schoeneberger et al (2021) estimate that the U.S. boiler population consists of approximately 38,500 units with a total cumulative capacity of 490 GW input. As per their estimates, the total industrial boiler capacity has increased by approximately 6% in recent years compared to the level in 2005 (EEA, 2005;Schoeneberger et al, 2021). Nearly half of the total number of boilers are less than 3 MW capacity however, these small boilers account for only 5% of the total capacity.…”
Section: Co 2 Emissions In Industrial Boilers and Electricity Generationmentioning
confidence: 99%
See 1 more Smart Citation